Cryopreservation of rhizome buds of Asparagus officinalis L. (cv. Morado de Huétor) and evaluation of their genetic stability - Carmona Martín, Elisabeth; Regalado, José Javier; Perán-Quesada, Rosa Amelia; López Encina, Carlos (Springer Nature, 2018)
We describe an encapsulation–dehydration procedure with prefreezing steps for the cryopreservation of rhizome bud explants of Asparagus officinalis L. cv. Morado de Huétor. With this procedure, survival of Rhizome buds was at least 84 and 42% developed to complete plantlets at 8 weeks. Flow cytometry and EST-SSR molecular markers were used to assess genetic stability of the regenerated material. Effects of preculture time in a medium rich in sucrose and prefreezing treatments (0 °C or/and − 20 °C) on plant recovery were evaluated. Rhizome Buds of the “Morado de Huétor” landrace were incubated in preculture medium (MS + 0.3 M sucrose) for 48 h, encapsulated in alginate beads and desiccated until a water content of 35%, prefrozen for one hour at 0 °C plus one hour at − 20 °C, followed by cryopreservation in liquid nitrogen, and then were rewarmed and recovered in ARBM medium for 6 weeks and finally incubated in ARBM-0 for 4 weeks. Analyses of ploidy and molecular stability of plantlets recovered from cryopreserved rhizome buds of two selected genotypes showed no differences compared with the mother plants. Cryopreservation of RB explants of A. officinalis with this Encapsulation–Dehydration procedure will be useful in long-term preservation programs.
https://openpolicyfinder.jisc.ac.uk/id/publication/16214?from=single_hit
Keywords: Espárragos; Crioconservación; Marcadores biológicos; Encapsulation–dehydration; Asparagus; Rhizome bud; Cryopreservation; Molecular markers; Flow cytometry